DEVELOPMENT OF PHYSICS TOOLS TO DETERMINE THE FRICTION COEFFICIENTS OF MATERIAL AND THE CAUSES OF ITS OCCURRENCE - MUNTI'AH ROHAYATI (NIM: 20207053), TITIK
This research is aimed to use simple physics tools to measure the static and kinetic friction coefficients of various materials. The results show that the static friction coefficient for the investigated materials are in the range of 0.214-0.469, and the kinetic friction coefficient are in the range of 0.171-0.371. The maximum static force related to maximum static friction coefficient obtained in this study vary between 0.118-2.549 Newton, and the stopping mass which is proportism to stopping force are in the range of 0.061-0.1255 kilograms.